Features of the functioning of retail trade enterprises as an element of the logistics system ("Journal "U". Economy. Management. Finance.", 2025)
The article examines the main features of a retail trading company as a logistics system. Effective logistics management and focus on the quality of goods are the key not only to the fruitful operation of a retail company, but also to its long-term development.
Keywords: retail company; logistics system; product; logistics; consumer